DIGITAL PUBLIC RELATIONS MELALUI AKUN INSTAGRAM @kb.kreditplus DALAM MEMPUBLIKASI PRODUK PERUSAHAAN DI PT KB FINANSIA MULTIFINANCE - Salsabila, Natasya; Kurniasari, Ni Gusti Ayu Ketut (Widya Aksara : Jurnal Agama Hindu, 2025)
Instagram is a social media that can be developed by public relations practitioners as a medium for publishing company products. The purpose of this study was to determine how the management of digital public relations through the @kb.kreditplus Instagram account in publicizing company products at PT KB Finansia Multi finance using The Circular Model of SOME. The approach used in this research is a qualitative approach. In this study, researchers used a qualitative descriptive method. The results of the study found that at the share stage, Kreditplus builds two-way communication with the audience through active interaction in the comments column and direct message (DM), and consistently shares product and service information. The optimize stage is carried out by following digital trends and adjusting content to make it more interesting and relevant to the audience, including the KOL Marketing strategy by collaborating with influencers. In the manage stage, Kreditplus implements media monitoring by determining the best time to upload content to increase interaction. However, there are still obstacles in responding quickly to direct messages (DM) which can have an impact on customer satisfaction. Meanwhile, the engage stage is carried out by presenting content that matches audience preferences, such as promotions and giveaways, to increase engagement and build customer loyalty.